The Impact of Industrial Agglomeration on Carbon Emissions: Empirical Evidence from China - Wen, Ya; Liao, Meng (International Journal of Management and Sustainability, 2019)
Based on panel data of China from 2004 to 2016, this paper explored the spatial spillover effect in industrial agglomeration and carbon emissions by using a spatial econometric model. Our results showed that industrial agglomeration significantly increases the carbon emissions in the local region, while inhibits the carbon emissions in the neighboring areas. After considering the choice of different spatial weight matrices, the conclusion is still robust. Further tests show that, on the one hand, industrial agglomeration can increase local carbon emissions and restrain them in the neighboring regions by increasing the industrial scale. On the other hand, industrial agglomeration suppresses the carbon emissions of local and neighboring areas by influencing the intensity of energy consumption. Moreover, the emission decrease effect of industrial agglomeration on the local part through the energy intensity is stronger than that in the vicinity. We propose that the government should coordinate the impact of industrial agglomeration on pollution emissions through both scale and energy effects. Maximize the role of energy saving and emission reduction in industrial agglomeration.